Test on the Antioxidant Activities of Methanol Extract of Bidara Leaves (Ziziphus spina-christi L.) using the DPPH Radical Immersion Method - Dwi Bagus Pambudi; Nuniek Nizmah Fajriyah; Vidiah Rizka Shalekhah (Borneo Journal of Pharmacy, 2020)
Bidara (Ziziphus spina-christi L.) is a tropical tree originating from Sudan in which it is commonly known as "Nebeq" in Saudi Arabia. It is of a bioactive compound - a flavonoid compound, which is the potential to be used as an antioxidant. It is capable of inhibiting any cell damages caused by free radicals. This study aimed to measure the activities of the free radicals in methanol extracts of Z. spina-christi leaves. The process of extracting the Z. spina-christi leaves was carried out through the maceration method using methanol as a solvent. The qualitative analysis of chemical compounds with certain eluents using thin-layer chromatography (TLC) was purposely to determine the groups of active compounds in extracts. The measurement of antioxidant activities was carried out using the 1,1-Diphenyl-2-picryl Hidrazyl (DPPH) immersion method in which absorption was measured at a maximum wavelength of 513 nm. The results showed that the methanol extract of Z. spina-christi leaves had a very weak antioxidant activity with the IC50 value of 466.804 μg/ml. The results of the bioautographic profile showed the presence of flavonoid compounds, phenols, saponins, and tannins.